Assessing the rate of torque development in sprint cycling: a methodological study - Connolly, S.; Peeling, P.; Binnie, M. J.; Goods, P. S.; Blazevich, A. J.; Timmerman, W. P.; Abbiss, C. R. (European Journal of Sport Science, 2023)
The present study examined (i) the magnitude of the rate of torque development (RTD) and (ii) the between-day reliability of RTD at the start of a cycling sprint when sprint resistance, sprint duration, and the pedal downstroke were altered. Nineteen well-trained cyclists completed one familiarisation and three testing sessions. Each session involved one set of 1-s sprints and one set of 5-s sprints. Each set contained one moderate (0.3 N m/kg), one heavy (0.6 N m/kg), and one very heavy (1.0 N m/kg) resistance sprint. RTD measures (average and peak RTD, RTD 0-100 ms, and RTD 0-200 ms) were calculated for downstroke 1 in the 1-s sprint. For the 5-s sprints, RTD measures were calculated for each of the first three downstrokes, as an average of downstrokes 1 and 2, and as an average of downstrokes 2 and 3. Whilst RTDs were greatest in downstroke 3 at all resistances, the greatest number of reliable RTD measures were obtained using the average of downstrokes 2 and 3 with heavy or very heavy resistances, where average and peak RTD, and RTD 0-200 ms were deemed reliable (ICC = 0.8, CV = 10%). Since only 1-2 downstrokes can be completed within 1 s, the greatest RTD reliability cannot be achieved using a 1-s sprint; therefore, the average of downstrokes 2 and 3 during a >2-s cycling sprint (e.g. 5-s test) with heavy or very heavy resistance is recommended for the assessment of RTD in sprint cyclists.